Incidence of amlodipine-induced gingival overgrowth in the rural population of Loni - Avneesh Tejnani; Ameet Mani; Neha Kaur Sodhi; Alok Mehta; Sonal Gourkhede; Vinayak Thorat; Pramod Marawar (Wolters Kluwer Medknow Publications, 2014)
Aims: Since the incidence of gingival overgrowth induced by amlodipine remains poorly defined, this study was carried out with an aim to determine the incidence. Materials and Methods: Dental patients who received amlodipine (N = 115), for more than 3 months were studied to determine the drug-induced gingival overgrowth. Clinical diagnosis of drug-induced overgrowth was verified by disappearance or decreased severity of gingival overgrowth after withdrawal of the causative drug. Results: The prevalence rate of amlodipine-induced gingival hyperplasia among experimental patients was 3.4%, while it was not observed among the control subjects. Oral examination revealed gingival overgrowth as a lobular or nodular enlargement on interdental papilla located in the anterior interproximal regions. Conclusions: In this study, there was a significant relationship between gingival inflammation resulting from dental plaque and drug dosage, and hyperplasia.